Sensitivity of ocean oxygenation to variations in tropical zonal wind stress magnitude. Issue 9 (3rd September 2014) - Ridder, Nina N.; England, Matthew H.
Abstract Ocean oxygenation has been observed to have changed over the past few decades and is projected to change further under global climate change due to an interplay of several mechanisms. In this study we isolate the effect of modified tropical surface wind stress conditions on the evolution of ocean oxygenation in a numerical climate model. We find that ocean oxygenation varies inversely with low‐latitude surface wind stress. Approximately one third of this response is driven by sea surface temperature anomalies; the remaining two thirds result from changes in ocean circulation and marine biology. Global mean O2 concentration changes reach maximum values of +4 μM and −3.6 μM in the two most extreme perturbation cases of −30% and +30% wind change, respectively. Localized changes lie between +92 μM under 30% reduced winds and −56 μM for 30% increased winds. Overall, we find that the extent of the global low‐oxygen volume varies with the same sign as the wind perturbation; namely, weaker winds reduce the low‐oxygen volume on the global scale and vice versa for increased trade winds. We identify two regions, one in the Pacific Ocean off Chile and the other in the Indian Ocean off Somalia, that are of particular importance for the evolution of oxygen minimum zones in the global ocean.